ANALYSIS OF THE PERMISSIBILITY OF BAI' AL-'INAH TRANSACTIONS ACCORDING TO THE SHAFI'I SCHOOL OF THOUGHT AND ITS IMPLEMENTATION IN MALAYSIA - Setiyadi, Alif Cahya; Mohammad Aris, Sakiinah (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2023)
This research aims to study the analysis of the ability of the bai' al-'inah contract according to the Syafi'i school and also how it is implemented in Malaysia. The author uses the qualitative research method of the literature type. The research results found that the contract of bai' al-'inah allowed by Imam Shafi'i is a contract that is free from the element of riba and other elements that can prohibit it. Among the conditions set by Imam Syafi'i are that the two sales and purchase transactions contained in this bai' al-'inah must stand alone and not be related to each other so that the second transaction is a condition for the first transaction. The Syariah Advisory Council (MPS) in Malaysia decided to allow bai' al-'inah based on the opinion brought by Imam Syafi'i. In the decision that has been issued, MPS states the conditions that must be followed by Islamic Banking Institutions in Malaysia that apply bai' al-'inah in their products. Among them are the two purchase and sale contracts, which must be clear and carried out separately; there is no repurchase condition in the contract, the time for the confirmation of the two contracts is different, and the transfer of ownership of assets is clear. This research concludes that the bai' al-'inah contract practised in Malaysia is permissible, according to Imam Syafi'i's opinion.